Kedisiplinan Siswa Melalui Hukuman Dalam Perspektif Stakeholder Pendidikan - Muhammad Husnur Rofiq (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
Purpose-This study aims to provide a common understanding between education stakeholders regarding student discipline through punishment. Design / methodology / approach- This research belongs to descriptive qualitative research, so the researcher tries to have a stock of theory and extensive insight so as to be able to inquire, analyze, and construct the social situation being studied becomes clearer and meaningful. Findings-Student discipline becomes one problems in education. The focus in this study is disciplinary education through punishment. Schools as educational institutions, teachers, parents, students, and the community have different understanding in understanding the discipline. Originality-punishment is a way to direct a behavior to match what is expected, but rewarding is more effective for the formation of student behavior than punishment.